The rise of the virtual state wealth and power in the coming century - Rosecrance, Richard N. 1930- (Basic Books, 1999)
"Explains what international relations and commerce will look like in the world of the next century. Rosecrance defines how this world will emerge, how the United States will figure in this new system of international politics and economics and who are the likely winners and losers on the coming international scene". -- Jacket.
Keywords: Estado, El; Internationale economische betrekkingen; Internationalisatie; Macht; Pouvoir (Sciences sociales); Relaciones económicas internacionales; Relations économiques internationales - Aspect politique; Seguridad internacional; Sécurité internationale; Toekomstverwachtingen; État; Globalisierung; Politik; Weltwirtschaft; International economic relations -- Political aspects; Power (Social sciences); Security, International; State, The; Wirtschaftliche Sicherheit; Strukturwandel; Kollektive Sicherheit